2005
DOI: 10.1158/1078-0432.ccr-04-2014
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Epigallocatechin Gallate and Polyphenon E Inhibit Growth and Activation of the Epidermal Growth Factor Receptor and Human Epidermal Growth Factor Receptor-2 Signaling Pathways in Human Colon Cancer Cells

Abstract: Purpose: (À)-Epigallocatechin gallate (EGCG) inhibits activation of the epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor-2 (HER2) and multiple downstream signaling pathways in cancer cell lines. In this study we compared the cellular and molecular effects of EGCG with a well-standardized decaffeinated green tea catechin mixture Polyphenon E (Poly E) on human colon cancer cell lines. Experimental Design and Results: Both EGCG and Poly E preferentially inhibited growth of the Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
245
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 309 publications
(261 citation statements)
references
References 34 publications
16
245
0
Order By: Relevance
“…49 Since we found that relatively low concentrations of actein can cause synergistic inhibition of the proliferation of breast cancer cells when combined with chemotherapy agents, actein might enhance the efficacy of other agents with respect to breast cancer prevention and therapy. 48 …”
Section: Discussionmentioning
confidence: 96%
“…49 Since we found that relatively low concentrations of actein can cause synergistic inhibition of the proliferation of breast cancer cells when combined with chemotherapy agents, actein might enhance the efficacy of other agents with respect to breast cancer prevention and therapy. 48 …”
Section: Discussionmentioning
confidence: 96%
“…2 family, which are frequently overexpressed in several types of human cancers, including cancers of the lung (1), head and neck (2), prostate (3), breast (4), pancreas (5), and colon (6), have been associated with abnormal growth of these tumors. It is well known that exposure of cells to EGF results in rapid autophosphorylation of EGFR molecules at the cell surface (7)(8)(9)(10), which upon activation lead to cell proliferation, motility, and enhanced survival (11).…”
Section: Members Of the Egf Receptor (Egfr)mentioning
confidence: 99%
“…Shimizu et al [30] have reported that EGCG (at 10-20 µg/mL) was shown to inhibit the activation of the EGFR, HER2, and multiple downstream signaling pathways in colon cancer cell lines. Tachibana et al [31] found that EGCG bound to a specific metastasis associated 67kDa laminin receptor that was expressed on a variety of tumor cells.…”
Section: A Interference With Intracellular Signaling Pathway (Figurmentioning
confidence: 99%